Factors that influence length of stay in starred and non-starred hotels in Padang city - Riri, Utari Ritma; Kasmita, Kasmita (Universitas Merdeka Malang, 2025)
As one of the fastest-growing industries, the hotel industry is a pivotal part of the tourism industry. A hotel's success in tourism development can be measured, among other things, by the length of stay guests maintain. Therefore, this study aims to map and deeply understand the factors influencing guests’ decisions to extend their stay in both star-rated and non-star hotels in Padang City. The exploration in this study is intended to build a conceptual understanding based on guest experiences and verify the alignment of field findings with consumer behavior and service quality theories. Using a qualitative approach, data were collected through in-depth interviews with 15 hotel guests selected purposively, representing various accommodation categories, during the period of March to May 2024. The results indicate five main factors affecting the length of stay: hotel facilities, service quality, pricing, location, and emotional experience. These findings are supported by the perceived value theory (Zeithaml, 1988), which suggests that consumer decisions are influenced by the perceived benefits relative to the costs incurred. Furthermore, the role of online reputation as a form of social influence reinforces the findings of Long (2022) regarding the impact of online reviews on accommodation preferences. Star-rated hotels tend to attract guests with complete facilities and professional services, while non-star hotels rely more on affordable pricing and friendly staff. The main contribution of this study lies in offering a locally grounded perspective on hotel guest behavior in Indonesia, particularly in Padang, while also providing strategic insights for hotel managers to design more adaptive and personalized services. These findings offer practical implications for enhancing guest loyalty and encouraging extended stays by strengthening key service aspects aligned with guest motivations and expectations.